PENGARUH LOYALITAS MEREK, RUMOR, DAN COUNTRY OF ORIGIN TERHADAP KEPERCAYAAN MEREK - Jony Oktavian Haryanto; Tirza Florence Manurip (Universitas Trisakti, 2011)
In this globalization era, the brand competition can not be avoided from the marketers to be able to keep their products loved by consumers. Therefore, the marketers have to create strategy to make the consumers trust in their brand product so they could compete in the marketplace because brand trust is so important. There must be positive value from a brand so that consumers will always be loyal to consume it because brand loyalty is so influential to brand trust.